ANALISIS KETAHANAN HIDUP PENDERITA DENGUE HEMORRHAGIC FEVER (DEMAM BERDARAH) DENGAN REGRESI COX KEGAGALAN PROPORSIONAL SENSOR TIPE III Studi Kasus di Rumah Sakit Umum Daerah (RSUD) Temanggung - Irfan Afifi; Di Asih I Maruddani; Abdul Hoyyi (Jurnal Gaussian, 2017)
Dengue Fever is a disease caused by the dengue virus, transmitted from person to person through the bite of Aedes Aegypti and Aedes Albopictus mosquitoes. Dengue Fever mainly found in the tropical countries, such as Indonesia. According to World Health Organization (WHO) data, Indonesia reported as the 2nd country with the largest dengue cases among 30 endemic countries between 2004 until 2010.  Therefore, it is important to identify the factors influencing the recovery speed of dengue patients. This study utilize statitistical approach through regression analysis. One of the analysis methode choosen is survival analysis. This analysis is utilized to figure out the time series data analysis, of origin undefined time until the occurrence of certain events. In Survival Analysis, one of the regression method which is commonly used is  Cox regression. This study uses statistical methods approach through Cox regression proportional hazard to take into consideration the time of failure as the dependent variable. as well as the response variable function tends to a constant failure. object of research in this study are patients with dengue fever and the time the patient entered in a separate viewing the selected sensor type III This study used medical records of dengue fever patients of regional public hospital in Temanggung City, Central Java, from period of January to November 2016. Results obtained shows that the factors affecting the recovery speed of patients is Hematocrit state of the patient. Patients with normal Hematocrit state have faster recovery that patients with upnormal circumtances.  Keywords: Dengue, Survival Analysis, Regression Cox Proportional Hazard